Impact Of Quality Courseware on Effective E-Learning - Saif M. Duhaim; Zahraa H. Ghadhban (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Courseware is an effective and important teaching and learning model, and it is at the core of the process of creating e-learning. The objective of this paper is to show effect of quality courseware on effective e-learning. A quantitative research approach by questionnaire has been utilized. A total 90 participants have been surveyed with the use of the questionnaire. This study shows that quality courseware was the most significant positive factor and more import e learning success.